2017
DOI: 10.1073/pnas.1612730114
|View full text |Cite
|
Sign up to set email alerts
|

SNX-1 and RME-8 oppose the assembly of HGRS-1/ESCRT-0 degradative microdomains on endosomes

Abstract: After endocytosis, transmembrane cargo reaches endosomes, where it encounters complexes dedicated to opposing functions: recycling and degradation. Microdomains containing endosomal sorting complexes required for transport (ESCRT)-0 component Hrs [hepatocyte growth factor-regulated tyrosine kinase substrate (HGRS-1) in Caenorhabditis elegans] mediate cargo degradation, concentrating ubiquitinated cargo and organizing the activities of ESCRT. At the same time, retromer associated sorting nexin one (SNX-1) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 98 publications
6
102
0
1
Order By: Relevance
“…with sequential-acquisition setting. Approximately ten images were taken in 1 μm sections from the top to the bottom of the beads [30,31]. Additionally, STORM/PALM was set up on an Olympus IX73 with an LED excitation light source as previously described [31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…with sequential-acquisition setting. Approximately ten images were taken in 1 μm sections from the top to the bottom of the beads [30,31]. Additionally, STORM/PALM was set up on an Olympus IX73 with an LED excitation light source as previously described [31].…”
Section: Methodsmentioning
confidence: 99%
“…Five thousand images were acquired for each field of view. Blinking events were identified by the change in fluorescence at individual pixels [31]. Centroid determination and image reconstruction were completed using QuickPALM [32].…”
Section: Methodsmentioning
confidence: 99%
“…Nigral Lewy bodies were also found to be co‐localized with RME‐8 (Vilarino‐Guell et al ). Unlike other DNAJC proteins implicated in PD, in vitro studies have revealed that the DNAJC13 mutation confers toxic gain‐of‐function, leading to E‐L cargo trafficking deficits (Norris et al ). The DNAJC13 mutation is also predicted to affect overall endosomal trafficking, even in the soma and postsynaptic compartment (Vilarino‐Guell et al ), unlike the synapse‐specific dysfunction predicted for auxilin.…”
Section: Clathrin‐mediated Synaptic Vesicle Endocytosis: a Prime Target?mentioning
confidence: 99%
“…The limiting membrane of endosomes is considered to comprise a patchwork of different functional protein-based and lipid-based domains. These include the aforementioned degradative subdomain, enriched with the components of the ESCRT machinery, and the retrieval subdomain, enriched with retromer and other cargoretrieval complexes [60][61][62]. The WASH complex is thought to contribute to the segregation between these two functional opposing subdomains by: i) structuring the retrieval subdomain through interaction with multiple cargo-selective elements and, ii) assembling a meshwork of branched filamentous actin to restrict the lateral mobility of these components and associated cargoes [3] (Figure 2).…”
Section: Actin and Wash In The Organization Of The Retrieval Subdomainsmentioning
confidence: 99%